A Meta-Analysis of Interleukin-10-1082 Promoter Polymorphism Associated with Gastric Cancer Risk - Ni, Peihua (Mary Ann Liebert, Inc., 2012)
We aimed to explore the role of allele A/G single nucleotide polymorphism (SNP) of gene Interleukin 10 (IL-10) promoter-1082 in the susceptibility to gastric cancer through a systematic review and meta-analysis. Each initially included article was scored for quality appraisal. Desirable data were extracted and registered into databases. Twenty studies were ultimately eligible for the meta-analysis of IL-10-1082 A/G SNP. We adopted the most probably appropriate genetic model (dominant model), with the combined group of GG-plus-GA genotypes compared with the AA genotype. Potential sources of heterogeneity were sought out via subgroup analyses and sensitivity analyses, and publication biases were estimated. Between IL-10-1082 GG-plus-GA genotypes with the risk of developing gastric cancer, statistically significant association could be noted with overall gastric cancer, being mainly in Asian subgroup, large sample subgroup, high quality subgroup, intestinal-type subgroup, cardia-type subgroup, and some genotyping method subgroups. Our meta-analysis indicates that IL-10-1082 GG-plus-GA genotypes are associated with the overall risk of developing gastric cancer and seem to be more susceptible to overall gastric cancer in Asian populations. IL-10-1082 GG-plus-GA genotypes are more associated with the pathologically intestinal-type gastric cancer or anatomically cardia-type gastric cancer.